Diachronic and Synchronic Analysis - the Case of the Indirect Object in Spanish - Dam, Lotte; Jensen, Helle Dam (HERMES - Journal of Language and Communication in Business, 2007)
This review article deals with a monograph on the indirect object in Spanish. The book offers a many-faceted analysis of the indirect object, as it, on the one hand, gives a detailed diachronic analysis of what is known as clitic-doubled constructions and, on the other, a synchronic analysis of both predicative constructions with an indirect object and the relationship between the notion of perspective and the indirect object. The general impression is that the author has produced an impressive analytical work, which, however, is not easily accessible.